2022
DOI: 10.1038/s41398-022-01799-z
|View full text |Cite
|
Sign up to set email alerts
|

Real-time individual benefit from social interactions before and during the lockdown: the crucial role of personality, neurobiology and genes

Abstract: Social integration is a major resilience factor for staying healthy. However, the COVID-19-pandemic led to unprecedented restrictions in social life. The consequences of these social lockdowns on momentary well-being are yet not fully understood. We investigated the affective benefit from social interactions in a longitudinal birth cohort. We used two real-time, real-life ecological momentary assessments once before and once during the initial lockdown of the pandemic (N = 70 participants; n~6800 observations)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Just recently, the relationship between social interactions and momentary well-being has addressed using ecological momentary assessment (EMA) 17 20 . Findings from these studies consistently indicate that physically being in the company strongly predicts higher levels of momentary well-being and positive mood 17 19 . However, little is known about how specific characteristics of social interactions (i.e., the social interaction partner, the self-perceived quality of the social interaction) are related to momentary well-being.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Just recently, the relationship between social interactions and momentary well-being has addressed using ecological momentary assessment (EMA) 17 20 . Findings from these studies consistently indicate that physically being in the company strongly predicts higher levels of momentary well-being and positive mood 17 19 . However, little is known about how specific characteristics of social interactions (i.e., the social interaction partner, the self-perceived quality of the social interaction) are related to momentary well-being.…”
Section: Introductionmentioning
confidence: 74%
“…Indeed, the amygdala has been recognized as a key region of the social brain 31 , with its particular involvement in social adaption and its high susceptibility to socioenvironmental influences 32 . Recently, it has been demonstrated that brain volume in the limbic circuit, which was previously linked to social affective benefit and social stress processing 31 , modulates the real-time affective benefit of being in company 19 , suggesting a possible involvement of neural markers on moment-level variables.…”
Section: Introductionmentioning
confidence: 99%
“…This is not in line with findings from Bernstein et al (2018), who used a study design with 6 semi-random prompts per day over three days upon which participants indicated social interaction and the pleasantness of that interaction, showing more happiness in situations with social interactions. Another study by Monninger et al (2022) linked social interactions to higher positive affect, but instead of asking the participants "live" in the situations, they indicated the number and quality of social contacts in the last 2 h prior to a prompt. It follows that the three approaches produce different findings, which leads to questions about the eligibility of the different assessment methods and the comparison of findings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, affective states represent wellbeing in different situations, as they are more sensitive to the respective influences and external factors in the specific situation (Brose et al, 2013). Underlining this, walking in both urban-and natural environments has been shown to be associated with higher positive affect and energy (Kinnafick and Thøgersen-Ntoumani, 2014), and social interactions are associated with higher positive affect, more happiness, and less tiredness in daily life (Bernstein et al, 2018;Monninger et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation